Transitioning from Child and Adolescent to Adult Psychiatric Care: Improving Outcomes after University Matriculation - D’Amelio, Giuseppe; Gold, Jessica A. (Current Psychopharmacology, 2021)
The transition from pediatric to adult psychiatric care is not well coordinated. Transitional age youths who are going to college for the first time experience a number of concomitant stressors, which make the transition of psychiatric care even more difficult. Given the burden of psychiatric illness in college students and the limited resources available, more investigation into feasible means of coordinating care needs to occur. Particularly as individuals with mental illness are most likely to experience lapses in care during this transition and have worse outcomes, being more likely to drop out of college.
Keywords: college transition